Analisis Tokoh Dan Penokohan Dongeng Sebagai Bahan Ajar Menceritakan Tokoh-Tokoh Pada Cerita Fiksi - Sulistiawati; Widjojoko; Deni Wardana (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2022)
In the Indonesian lesson, the purpose of speaking skills is so that students are able to communicate orally and in writing. One of the goals with students is able to tell orally or in writing the content contained in the text that has been read. This study is intended to analyze the characters and characters in a fairy tale book entitled "Romelu, Sumatran Elephant" which will then be made as teaching material for learning materials to tell the characters that can be found in the fictional text in class IV elementary school. This research is qualitative research and uses content analysis techniques because it analyzes each character and characterization of the fairy tale book entitled "Romelu, Sumatran Elephant". The subjects of this study are figures and characters in a fairy tale book entitled "Romelu, Sumatran Elephant". Based on the results of research obtained from three stages of analytical techniques, namely reducing data, describing data, and drawing conclusions, it can be seen that the results of the study are fairy tales entitled "Romelu, Sumatran Elephants" has 7 figures, consisting of the main character, namely Romelu Gajah, and additional figures, namely pelita, Riko Squirrel, Moura Musang, Jaya Ayam Jago, Romelu's parents, and Bondol Eagles. Of the seven characters contained in the fairy tale "Romelu, Sumatran Elephant" is a character with the character (characterization) of the protagonist. From the results of the research, teaching materials were made in the form of handouts containing teacher handle materials and student worksheets.